Pengaruh Pengungkapan Emisi Karbon, Inovasi Hijau, dan Investasi Hijau Terhadap Nilai Perusahaan - Aisyah Putri Nuurhasanat; Aqamal Haq (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the impact of carbon emission disclosure, green innovation, and green investment on firm value in the energy and infrastructure sectors. The analysis method used is panel data analysis. The data used are taken from the sustainability reports and annual reports of leading companies in the energy and infrastructure sectors listed on the Indonesia Stock Exchange (IDX) for the years 2021-2023. The research sample uses the purposive sampling method, resulting in a total of 153 selected samples. The results of the hypothesis testing show that the variable of carbon emission disclosure has a positive effect on firm value, while green innovation and green investment do not affect firm value. The implications of this research are (1) This study is expected to inspire future researchers. (2) It is hoped that companies will continue to voluntarily disclose carbon emissions, engage in green innovation, and make decisions regarding green investments. (3) It can encourage investors to pay more attention to environmental issues in their investment decision-making.